Eruptive Cycle and Bubble Trap of Strokkur Geyser, Iceland. Issue 4 (1st April 2021) - Eibl, Eva P. S.; Müller, Daniel; Walter, Thomas R.; Allahbakhshi, Masoud; Jousset, Philippe; Hersir, Gylfi Páll; Dahm, Torsten
Abstract: The eruption frequency of geysers can be studied easily on the surface. However, details of the internal structure including possible water and gas filled chambers feeding eruptions and the driving mechanisms often remain elusive. We used a multidisciplinary network of seismometers, video cameras, water pressure sensors and one tiltmeter to study the eruptive cycle, internal structure, and mechanisms driving the eruptive cycle of Strokkur geyser in June 2018. An eruptive cycle at Strokkur always consists of four phases: (1) Eruption, (2) post‐eruptive conduit refilling, (3) gas filling of the bubble trap, and (4) regular bubble collapse at shallow depth in the conduit. For a typical single eruption 19 ± 4 bubble collapses occur in Phase 3 and 8 ± 2 collapses in Phase 4 at a mean spacing of 1.52 ± 0.29 and 24.5 ± 5.9 s, respectively. These collapses release latent heat to the fluid in the bubble trap (Phase 3) and later to the fluid in the conduit (Phase 4). The latter eventually reaches thermodynamic conditions for an eruption. Single to sextuple eruptions have similar spacings between bubble collapses and are likely fed from the same bubble trap at 23.7 ± 4.4 m depth, 13–23 m west of the conduit. However, the duration of the eruption and recharging phase linearly increases likely due to a larger water, gas and heat loss from the system. Our tremor data provides documented evidence for a bubble trap beneath a pool geyser. Plain Language Summary: It is easy to study the eruptions of a geyser on the surface. It is however difficult to study the shape of the geyser at depth and the processes that cause eruptions since we cannot observe them directly. Here, we use seismometers, cameras, pressure sensors and one tiltmeter to study the behavior and area beneath pool geyser Strokkur, Iceland, in June 2018. We find that the geyser always passes through four phases: (i) eruption, (ii) refilling of the conduit with water, (iii) gas accumulation in a bubble trap, and (iv) bubbles leaving the bubble trap regularly to collapse in the conduit at shallow depth. Bubble collapses, heating and gas accumulation in the bubble trap takes place at a mean depth of 23.7 ± 4.4 m, 13–23 m west of the conduit (Phase 3). Phase 4 is characterized by regular bubble collapses at shallow depth in the conduit heating the fluids in the conduit to prepare for an eruption. Single to sextuple eruptions behave similar and are likely fed from the same bubble trap offset from the conduit. However, the eruption and recharging phase persists for longer most likely caused by a larger water, gas and heat loss from the system. Key Points: Eruptive cycle of Strokkur consists of eruption, conduit refilling, bubble trap gas accumulation and bubble collapses at depth in conduit Duration of phases in the eruptive cycle linearly increases from single to sextuple eruptions, except for the conduit refilling phase We infer a bubble trap at a pool geyser at 23.7 ± 4.4 m depth, 13–23 m west of the conduit feeding single to sextuple eruptions